2018
DOI: 10.1016/j.medmal.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care admission for Coronavirus OC43 respiratory tract infections

Abstract: As for MERS Co-V infections, underlying comorbidities impacted the clinical outcomes of OC43 infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…CoV-NL63 has recently been described to cause a fatal outbreak of SARI in a long-term care facility with a 27.7% infection rate and 1.5% lethality in Baton Rouge, Louisiana, USA [33]. Reports on hospital outbreaks of CoV-OC43 and CoV-HKU1 are scanty, and infections by these CoVs resulting in SARI are typically seen in frail subjects [34,35]. The propensity for nosocomial spreading and the dominant role played by symptomatic patients in the spreading of the infection are supported by basic virology.…”
Section: Hospital Outbreaks Of Non-sars-like Covsmentioning
confidence: 99%
“…CoV-NL63 has recently been described to cause a fatal outbreak of SARI in a long-term care facility with a 27.7% infection rate and 1.5% lethality in Baton Rouge, Louisiana, USA [33]. Reports on hospital outbreaks of CoV-OC43 and CoV-HKU1 are scanty, and infections by these CoVs resulting in SARI are typically seen in frail subjects [34,35]. The propensity for nosocomial spreading and the dominant role played by symptomatic patients in the spreading of the infection are supported by basic virology.…”
Section: Hospital Outbreaks Of Non-sars-like Covsmentioning
confidence: 99%
“…We have previously shown that the presence of coronavirus OC43 N-protein in the nasopharynx correlates with the respiratory tract infection symptoms 32 . It has been shown that clinical presentations of seasonal coronavirus OC43 infections can be similar to those of coronaviruses that are considered as severe viruses (SARS and MERS) 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Coronaviridae represent a very important family of animal and human viruses [1,2] that are in permanent circulation. Four common human coronaviruses (HKU1, NL63, OC43 and E229) cause 10-20% of respiratory infections worldwide and are present in all continents [3][4][5][6][7][8][9][10][11][12][13][14] ( Table 1). Mortality is poorly assessed, but it is clear that there are chronic carriers as well as asymptomatic carriers.…”
Section: Introductionmentioning
confidence: 99%